The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1002/gps.2461
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of carer distress in people with dementia

Abstract: The clinical implications of awareness of carer distress in people with dementia should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…People with early experience of dementia in this synthesis have demonstrated that they continue to work actively with others in their family to maintain their relationships; to make sense of the impact of dementia and to manage the changes that it brings. Consistent with previous research, the accounts of people with dementia demonstrate continued emotional awareness and awareness of the impact of dementia upon the family member involved in caring for them (Ablitt, Jones and Muers 2010; Burgener and Twigg 2002). Such insight and awareness facilitated opportunities for the relationship to continue to grow and for compromise and adjustment to take place, thus appearing to contribute to wellbeing and meaningful lives.…”
Section: Discussionsupporting
confidence: 78%
“…People with early experience of dementia in this synthesis have demonstrated that they continue to work actively with others in their family to maintain their relationships; to make sense of the impact of dementia and to manage the changes that it brings. Consistent with previous research, the accounts of people with dementia demonstrate continued emotional awareness and awareness of the impact of dementia upon the family member involved in caring for them (Ablitt, Jones and Muers 2010; Burgener and Twigg 2002). Such insight and awareness facilitated opportunities for the relationship to continue to grow and for compromise and adjustment to take place, thus appearing to contribute to wellbeing and meaningful lives.…”
Section: Discussionsupporting
confidence: 78%
“…Caregiver distress, both in relation to specific NPI-Q symptoms and more generally on the Relatives Stress Scale, was also associated with lower QoL as rated by the person with dementia, suggesting a sensitivity on the part of the person with dementia to the emotional climate, as has been demonstrated previously [54]. The carer’s NPI-Q distress rating relating to agitation/aggression did not however contribute additionally to the final model.…”
Section: Discussionmentioning
confidence: 49%
“…Scores of 11 or more on either subscale are considered to be a significant ‘case’ of psychological morbidity, with scores of 8–10 classified as ‘borderline’ and 0–7 ‘normal’. The HADS has been employed and validated in studies of people with dementia and carers [65,66]. …”
Section: Methodsmentioning
confidence: 99%